Logic of Nonsense and Pragmatics of Language Used in Lewis Carroll’s Alice’s Adventures in Wonderland - Saeed Saif Moqbel, Marwan (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
Lewis Carroll’s Alice’s Adventures in Wonderland is an adventure story that appeals to children as well as adults. While children are interested in the surface humour, adults are interested in the strange way of reasoning and the satire on many aspects of Victorian society. This paper aims at analyzing the conversations between Alice and the inhabitants of Wonderland to show how Lewis Carroll, through violating the well-established norms of logical argumentation and the pragmatics of conversation based on the Cooperative Principle of Grice (1975) and the Politeness Principle of Brown and Levinson (1978), was able to create humour and convey deeper messages. The paper highlights how the exchanges between Alice and the inhabitants of Wonderland turn out to be puzzling, and sometimes, even nonsensical and humorous because of the way language is used. It also shows that Carroll, through the nonsensical, yet seemingly logical, arguments of the inhabitants of Wonderland, was able to convey deeper messages, such as pointing out how confusing adults and their world are to children and how there is a gap in communication between them and mocking some aspects of the restrictive Victorian society. In this, the paper provides a deeper understanding of the language of Carroll’s Alice’s Adventures in Wonderland.